LASER DEPOSITION. THE AREA THERMAL FIELD - Florin CIOFU; Alin Nioata (Fiabilitate şi Durabilitate)
By laser direct deposition, the parts are manufactured by injecting powder in a melt metal bath with the help of the laser. During the manufacture it is deployed a complex “ thermic history” in the different built regions. This includes re-melting and many thermic cycles at low temperatures (of hundreds of degrees). The phenomena of thermic transmission are variable in time, being by excellence reversible phenomena, too, as the temperature difference which intervenes cannot be ever small infinite. In the most general case, the temperature is a function of space coordinates, and of the time ح